Photoacoustic Technology for Biological Tissues Characterization - Hui Ling, Chua; Huong, Audrey (Institute of Advanced Engineering and Science, 2020)
The existing PA imaging systems showed mixed performance in terms of imaging characteristic and signal-to-noise ratio (SNR). The aim of this work is to present the use of an in-house assembled photoacoustic (PA) system using a modulating laser beam of wavelength 633 nm for two-dimensional (2D) characterization of biological tissues. The differentiation of the tissues in this work is based on differences in their light absorption, wherein the produced photoacoustic signal detected by a transducer was translated into phase value (Ф) that corresponds to the peak amplitude of tissue optical absorption. This research investigated variation in PA response between the considered different parts of chicken carcasses: fat, liver and muscle. This work found fat tissue to produce the strongest PA signals with mean ± standard deviation (SD) Ф = 2.09 ± 0.31 while muscle produced the least signal strength with Ф = 1.03 ± 0.17. This work attributes these observations and the presence of stripes pattern in 2D Ф images of fat and muscle to the differences in the optical and structural properties of these samples. In addition, a comparison has been made in an attempt to better assess the performance of the developed system with the related ones.This work concluded that the developed system may be useful as an alternative means in the noninvasive and label-free visualization and characterization of intact biological tissues in terms of their structural and physiological context in the future.